Adaptations to relational facilitation for two national care coordination programs during COVID-19 - Sjoberg, Heidi; Kenney, Rachael R.; Morgan, Brianne; Connelly, Brigid; Jones, Christine D.; Ali, Hebatallah Naim; Battaglia, Catherine; Gilmartin, Heather M. (Frontiers in Health Services, 2022)
Background: Adaptations to implementation strategies are often necessary to support adoption and scale-up of evidence-based practices. Tracking adaptations to implementation strategies is critical for understanding any impacts on outcomes. However, these adaptations are infrequently collected. In this article we present a case study of how we used a new method during COVID-19 to systematically track and report adaptations to relational facilitation, a novel implementation strategy grounded in relational coordination theory. Relational facilitation aims to assess and improve communication and relationships in teams and is being implemented to support adoption of two Quadruple Aim Quality Enhancement Research Initiative (QA QUERI) initiatives: Care Coordination and Integrated Case Management (CC&ICM) and the Transitions Nurse Program for Home Health Care (TNP-HHC) in the Veterans Health Administration (VA). Methods: During 2021-2022, relational facilitation training, activities and support were designed as in-person and/or virtual sessions. These included a site group coaching session to create a social network map of care coordination roles and assessment of baseline relationships and communication between roles. Following this we administered the Relational Coordination Survey to assess the relational coordination strength within and between roles. COVID-19 caused challenges implementing relational facilitation, warranting adaptations. We tracked relational facilitation adaptations using a logic model, REDCap tracking tool based on the Framework for Reporting Adaptations and Modifications-Enhanced (FRAME) with expanded Reach, Effectiveness, Adoption, Implementation, Maintenance (RE-AIM) dimensions, and member checking. Adaptations were analyzed descriptively and for themes using matrix content analysis. Results: COVID-19’s impact within the VA caused barriers for implementing relational facilitation, warranting eight unique adaptations to the implementation strategy. Most adaptations pertained to changing the format of relational facilitation activities (n=6; 75%), were based on external factors (n=8; 100%), were planned (n=8; 100%) and initiated by the QA QUERI implementation team (n=8; 100%). Most adaptations impacted adoption (n=6; 75%) and some impacted implementation (n=2; 25%) of the CC&ICM and TNP-HHC interventions. Discussion: Systematically tracking and discussing adaptations to relational facilitation during the COVID-19 pandemic enhanced engagement and adoption of two VA care coordination interventions. The impact of these rapid, early course adaptations will be followed in subsequent years of CC&ICM and TNP-HHC implementation.